Pemaanfaatan Fasilitator BTPN Untuk Meningkatkan Pendapatan Nasabah Dalam Berwirausaha - Isabilillah, Alpiero Joeval; Nirawati, Lia (Universitas Gajah Putih, Indonesia, 2023)
This community service is carried out by the Assist Facilitator division which aims to assist the business development of PT. Bank BTPN Syariah. In business development it is important to understand the business business needs needed by customers such as providing material that is appropriate to the customer's business, analyzing market potential, increasing accessibility, as well as providing training and guidance to customers. The results of the community service carried out by the Assist Facilitator division show that PT. Bank BTPN Syariah has an important role in providing an E-learning platform that aims to help the needs of its customers